Pengaruh Konseling Behavioral Teknik Self-Management Untuk Meningkatkan Motivasi Belajar Siswa di SMA Negeri 4 Singaraja - Brema Cahyadi Sinuhaji; I Ketut Dharsana; Ni Ketut Suarni (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2023)
This study aims to determine the effect of behavioral counseling services with self-management techniques to increase student motivation at SMA Negeri 4 Singaraja. The method used in this study is an experiment with sampling using random sampling technique. The analysis technique used is parametric statistics using paired sample T-test. The research design used is the Non-Equivalent Control Group Design. In this study, it focuses on the influence of behavioral counseling services with self-management techniques to increase student motivation with data collection techniques used in the form of questionnaires.